Almost like being there? A conceptualisation of live-streaming theatre. Issue 2 (4th June 2018) - Mueser, Daniela; Vlachos, Peter
Abstract : Purpose: The live streaming of theatrical performances to cinemas has become increasingly common in recent years. The practice offers potentially positive returns for audience reach, audience development, revenue streams and global cultural exchange (Cochrane and Bonner, 2014; Nesta, 2011; King, 2016). However, the conceptualisation of live performance transmissions remains under-explored. The purpose of this paper is to review critically selected literature on event experience and apply it to the growing practice of live-streaming theatre (LST). In doing so, the paper develops a new conceptual model that can be used to guide future research on audience expectations, motivations and experience of LST. Design/methodology/approach: A comparative historic case study approach combines a structured review of relevant academic literature and industry sources. Theories of live cultural experience and authenticity are critically reviewed. The opportunities and threats of LST to performing arts companies are summarised. The approach considers cognitive, affective and behavioural factors in probing themes of audience awareness, perceptions, expectations and experience of LST. The paper uses these factors to develop an original conceptual model for LST. Findings: The research finds that the practice of cinematic live transmission of performing arts challenges existing conceptual categories and marketing strategies. Fundamental events studies factors such as "attendance", "authenticity" and "experience" are re-evaluated. The model suggests that despite improvements in digital technology traditional theatre and broadcasted theatre are two different experiences, not substitutes. Research limitations/implications: As a conceptual paper, the results are subject to being tested in the field. The findings reveal implications for the evolving future of hybrid and mixed event experiences. The potential for LST screenings to attract new audiences requires further study. Practical implications: The implications of the research reflect the changing business models and supply side dynamics of theatre production and touring. The results suggest that live streaming is of limited effectiveness in addressing the capacity limits of Baumol and Bowen's (1966) "cost disease" in live arts performance. LST allows major brands to penetrate regional markets thereby potentially squeezing out smaller touring companies and restricting innovation. Social implications: The findings reveal implications for the evolving future of hybrid and mixed event experiences. Originality/value: The influence of digital technology on live arts experience is currently under-explored and under-theorised. This paper develops a new conceptual model that captures in greater detail than previously the various factors that may determine audience engagement with, and experience of, LST. The paper contributes to knowledge by expanding the discourse on the gaps between the competing aims of access and authenticity. The analysis expands the academic understanding of hybrid and virtual event experiences.